LOW COST INCUBATION POT FOR BETTER HATCHING OF SILKWORM EGGS IN DRY SUMMER - SAHA, A. K.; DATTA (BISWAS), T.; SARATCHANDRA, B.; DAS, S. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Proper incubation of silkworm eggs play a vital role in silkworm rearing. 25°C temperature and 75-80% R.H. is ideal for incubation of silkworm eggs. The farmers do not have suitable devise for maintaining optimum temperature and humidity during incubation for obtaining uniform hatching and subsequently improvement in yield. The low cost incubation device developed is suitable for dry summer can reduce the temperature by 6-7°C and increase the humidity by 40% and thereby maintaining suitable environment for incubation of silkworm eggs. Hence, the method can be adopted at farmers' level.